Fast Green FCF Alleviates Pain Hypersensitivity and Down-Regulates the Levels of Spinal P2X4 Expression and Pro-inflammatory Cytokines in a Rodent Inflammatory Pain Model - Xu, Fang; Yang, Jing; Lu, Fan; Liu, Rongjun; Zheng, Jinwei; Zhang, Junfang; Cui, Wei; Wang, Chuang; Zhou, Wenhua; Wang, Qinwen; Chen, Xiaowei; Chen, Junping (Frontiers in Pharmacology, 2018)
Fast Green FCF (FGF), a biocompatible dye, recently drew attention as a potential drug to treat amyloid-deposit diseases due to its effects against amyloid fibrillogenesis in vitro and a high degree of safety. However, its role in inflammatory pain is unknown. Our study aimed to investigate the effect of FGF in the inflammatory pain model induced by complete Freund’s adjuvant (CFA) and to identify the associated mechanisms. We found that systemic administration of FGF reversed mechanical and thermal pain hypersensitivity evoked by CFA in a dose-dependent manner. FGF treatment decreased purinergic spinal P2X4 expression in the spinal cord of CFA-inflamed mice. FGF also down-regulated spinal and peripheral pro-inflammatory cytokines (tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6)), but did not alter the spinal level of nerve growth factor (NGF) or brain-derived neurotrophic factor (BDNF). In conclusion, our results suggest the potential of FGF for controlling the progress of inflammatory pain.